Platelet Indices in Patients with Coal Workers’ Pneumoconiosis - Uygur, Firat; Ornek, Tacettin; Tanriverdi, Hakan; Altuntas, Murat; Altinsoy, Bulent; Erboy, Fatma; Tor, Meltem; Atalay, Figen (Lung, 2016)
Purpose Coal workers’ pneumoconiosis (CWP) is caused by an accumulation of coal particles in the lung parenchyma. Reactive oxygen species (ROS) play an important role in the pathogenesis of CWP. It is well documented that ROS stimulate platelet activation, adhesion, and aggregation. The aim of the present study was to investigate the relationship between platelet indices and CWP. Methods The demographic features, occupational and medical history, exposure time, and complete blood count of retired coal miners were retrospectively analysed. The control group comprised healthy subjects who had not worked underground. Chest radiographs were evaluated according to the CWP classification of the International Labour Office. Results The study population was divided into following groups: 50 controls, 97 without CWP, 142 simple pneumoconiosis (SP), 157 progressive massive fibrosis (PMF). The platelet count, mean platelet volume (MPV), platelet distribution width (PDW), and plateletcrit (PCT) were significantly higher in patients with CWP compared to those in patients without CWP and controls. The platelet count, MPV, and PCT were higher in patients with PMF compared to those in the SP group ( p < 0.05). The results of multiple logistic regression analyses indicated that the platelet count, MPV, and PCT were independently associated with the development of CWP. Conclusions Platelet indices may be considered as disease markers for pneumoconiosis in coal miners and as a useful indicator of the progression of pneumoconiosis.